RESULTS OF EXPLORATORY PURSE SEINING BETWEEN COCHIN AND GOA - Shanmugavelu, C R; Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
Of the nine fishing squares covered along th« Cochin-Goa coast by the purseseiners operated by the Integrated Fisheries Project, Cochin, and the ExplorstoryFisheries Project at Mangalore and Goa during the period, January 1975 to June1978, the ansas 6-76, 10-76 and l'5-73, between the latitude 9°10'-15°40''N andlongitude 73°30'-76°30'E, were explored intensively. Out of the total of 10,81,951kg of fishes landed as a result, 72% of the catch comprisied of oil sardine